Peran Pembelajaran Ilmu Pengetahuan Sosial dalam Upaya Pencegahan Radikalisme di MTs NU TBS Kudus - Hafidhuddin, Muhammad Hilmi; Hermanto, Fredy (Sosiolium: Jurnal Pembelajaran IPS, 2021)
This study aims to determine efforts to prevent radicalism in schools through strengthening character in social science learning (IPS) and implementing strengthening character education (PPK) in extracurricular activities at MTS NU TBS Kudus. The results showed that schools were trying to prevent the development of radicalism. Prevention of radicalism in schools is carried out through the implementation of strengthening character education (PPK) through three activities, namely intracular activities, co-curricular activities, and extracurricular activities. Implementation in intraculricular activities focuses on social studies learning which has material and dimensions related to everyday life. Implementation in extracurricular activities focuses on implementing the vision and mission through school culture and school activities. Meanwhile, the results of the analysis of efforts to prevent radicalism through the implementation of character strengthening show that the implementation of PPK has been carried out and has had an impact, but in its implementation, there are still a number of obstacles, especially during the Covid-19 pandemic.